The surface characteristics and the vertical structure of the ITCZ over the Philippines on September 8-14, 2015 (case study) - GARING, EMMANUEL (Archīum Ateneo, 2018)
On September 8 14, 2015, an ITCZ developed over the Philippines, which brought rainfall all over the Philippines over this period. A composite analysis method was applied using the upper-air measurements from the University of Wyoming website. A ten-year mean sounding was used as a baseline to extract any distinctive features of the vertical profile of this ITCZ. For the surface, rainfall associated with this ITCZ were investigated using PAGASA's ground station measurements. The ITCZ axis was located over -10oN. Composite analysis shows that this ITCZ is warm and dry at the surface. The dry area at the surface was due to orographic rainout caused by the mountains of Mindanao area producing more rainfall slightly over the south of the axis. At higher altitudes, the trade wind inversion or TWI was observed. This TWI together with dry region of air aloft marks the location of the subsidence region. The complex terrain of the surface plays an important role in developing the ITCZ. The rainfall on the ITCZ axis is more intense at the axis of the ITCZ compared to the areas northern and southern regions of the ITCZ. The region of subsidence is responsible for the decreased rainfall at some areas north of the ITCZ. On the western part of the Philippines, most intense rainfall was observed however, this was likely due to the active southwest monsoon together with the formation of a tropical storm.